تعليم الألسنية الحديثة لأغراض خاصة =(Ta'lim al-Alsuniyyah al-Hadithah Li Aghradh Khassah) - Dollah, Nafi@Hanafi; Ali, Asem Shehadeh Saleh; Haji Ibrahim, Majdi; Hj. Yaakub, Muhamadul Bakir; Ismail, Yasir (IIUM Press, 2013)
Series of books in ICALL 2013 for Linguistics